Regeneration of poly-L-lysine modified carbon electrodes in the accumulation and cathodic stripping voltammetric determination of the cromoglycate anion - Pereira, F. C.; Fogg, A. G.; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V., 2003)
Cromoglycate is accumulated on a poly-L-lysine (PLL) modified carbon electrode best from pH 4 solution, where it is anionic and the PLL is cationic, and at which pH the cromoglycate gives a good reduction peak at -0.82 V. The PLL film can be regenerated readily by washing the electrode with 3 M sodium hydroxide solution, in which the PLL is deprotonated. Regeneration of the film is not required as frequently when larger amounts of PLL are incorporated into it. This allows standard addition procedures to be carried out without regenerating the electrode. Linear calibration graphs have been obtained typically in the range 0.1 - 1.5 mug ml(-1). Detection limits have been calculated to be 10 ng ml(-1). The standard addition method has been applied satisfactorily to diluted urine solutions. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: poly-L-lysine; sodium cromoglycate; modified electrodes; electroanalysis